THE MODERN VIEWS ON THE PROBLEM OF DIAGNOSING CHRONIC TONSILLITIS OF CYTOMEGALOVIRUS AETIOLOGY - Rustamova R.; Kudratova Z. E. (Web of Journals Publishing, 2025)
Currently, there are a lot of works devoted to the problem of chronic tonsillitis and adenoiditis. Chronic tonsillitis is one of the main problems of otorhinolaryngology and paediatrics and accounts for 74% according to some authors. The analysis of foreign and domestic literature has shown an important role of viral infections in the development of chronic tonsillitis and adenoiditis in children [1].
Keywords: Chronic tonsillitis, infection, organism, health, viral infection.